Is the Friedman Rule Stabilizing? Some Unpleasant Results in a Heterogeneous Expectations Framework - Mattia Guerini (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2013)
The recent economic crisis gave proof of the fact that the Taylor rule is no more that good instrument as it was thought to be just ten years ago; this might be due to the fact that agents acting in the economy hold Heterogeneous Expectations (HE). In a recent paper Anufriev et al. (2013) suggest that a way to force stability on the economic system is to adopt a more aggressive Taylor rule. In the present paper a standard NK-DSGE is considered in order to investigate whether a Friedman k-percent monetary policy rule may be a valid instrument to counteract the instability created by the presence of HE in a framework à la Brock and Hommes (1997). The model here presented suggests that when such a money supply rule is adopted by the Central Bank, stability strongly depends on the intensity of choice, which represents the ability of the agents to switch toward the best available predictor.
Keywords: E37; E52; E58; 330; Heterogeneous Expectations; Friedman Monetary Policy Rule; Macroeconomic Stability